Repertoires of Terrorism in Mexico’s Criminal War - Feldmann, Andreas E. (Perspectives on terrorism, 2022)
Security conditions in Mexico linked to the confrontation between security forces, organized crime groups (OCGs) and self-defense groups have deteriorated due to the rise of terrorist attacks. While Mexico has a history of violence, terrorism has not been a common practice. This article provides a brief analysis of existing trends by examining the nature of terrorism in Mexico and reviewing the way in which different armed parties utilize this tactic. It argues that terrorism arises in the context of a criminal war in which state security forces, self-defense groups and different OCGs have developed specific repertoires of terrorism that fit their organizational goals and character.